A reliability study of isometric shoulder internal and external rotation strength in young badminton players using a hand-held dynamometry - Abdullah, Borhannudin; Samsudin, Shamsulariffin; Gasibat, Qais; Mohd Nasirudddin, Nasnoor Juzaily (Editura Universitatea din Pitesti, 2023)
Accurate measurement of internal rotation and external rotation (IR/ER) muscle strength is crucial for badminton players, coaches, and support staff to ensure appropriate training prescription and reduce the risk of injuries. Previous studies have highlighted the significance of measurement position and stabilisation in achieving reliable outcomes. This study aimed to assess the reliability of Hand-Held Dynamometry (HHD) in measuring shoulder IR/ER strength among young club badminton players using the Microfet 2„¢ dynamometer. Thirty young badminton players aged 17.4±1.8 years, with a body mass of 56.08±5.7 kg, participated in the study. Isometric strength tests (ISTs) for shoulder IR/ER were conducted using the Microfet 2„¢ dynamometer. To determine the reliability, the same strength tests were repeated two days apart for each participant. The results demonstrated high reliability for both IR (ICC = 0.92-0.91) and ER (ICC = 0.99“0.96) in both dominant and non-dominant shoulders. Additionally, the percentage of Smallest Real Difference (SRD) remained consistently below 20 for IR and below 12 for ER in both shoulders. The ER/IR ratio also showed good reliability (ICC = 0.83 and 0.82) for both dominant and non-dominant shoulders. The findings of this study indicate that HHD using the Microfet 2„¢ is a reliable tool for measuring shoulder IR/ER strength in young badminton players. The high reliability and low SRD percentages suggest that the device can yield consistent results, which is essential for accurate training prescription and injury prevention. The use of the Microfet 2„¢ dynamometer in measuring shoulder IR/ER strength among young badminton players is supported by the high reliability demonstrated in this study. Coaches, players, and support staff can confidently utilize this tool to optimize training programs and minimize the risk of injuries in this population.